The dying citizen ebook How progressive elites, tribalism, and globalization are destroying the idea of america. - Hanson, Victor Davis (2021)
The New York Times bestselling author of The Case for Trump explains the decline and fall of the once cherished idea of American citizenship. Human history is full of the stories of peasants, subjects, and tribes. Yet the concept of the “citizen” is historically rare—and was among America’s most valued ideals for over two centuries. But without shock treatment, warns historian Victor Davis Hanson, American citizenship as we have known it may soon vanish. In The Dying Citizen , Hanson outlines the historical forces that led to this crisis. The evisceration of the middle class over the last fifty years has made many Americans dependent on the federal government. Open borders have undermined the idea of allegiance to a particular place. Identity politics have eradicated our collective civic sense of self. And a top-heavy administrative state has endangered personal liberty, along with formal efforts to weaken the Constitution. As in the revolutionary years of 1848, 1917, and 1968, 2020 ripped away our complacency about the future. But in the aftermath, we as Americans can rebuild and recover what we have lost. The choice is ours.